Polymorphisms of inflammation-related genes and susceptibility to childhood leukemia: evidence from a meta-analysis of 16 published studies - Qiuping Zeng; Haoyan Ren; Cui Liu; Ting Liu; Yongwu Xie; Xiufu Tang (Hematology, 2023)
ABSTRACTObjective: This study was to comprehensively clarify the associations between single nucleotide polymorphisms (SNPs) in inflammatory genes and the susceptibility to childhood leukemia.Methods: Eligible articles were collected from the databases of PubMed, EMBASE, Cochrane Library, CNKI and Wan Fang. The pooled odds ratios (ORs) and 95% conﬁdence intervals (95% CIs) were calculated to estimate the association strength by using the STATA 15.0 software.Results: Sixteen studies were enrolled. These studies mainly evaluated SNPs in 13 genes, including C-X-C motif chemokine ligand 12 (CXCL12), toll-like receptor (TLR)−4, TLR6, TLR9, CD14, interleukin (IL)−1β, NLR family pyrin domain containing 3, IL-4, interleukin 4 receptor, IL-10, IL-13, macrophage migration inhibitory factor (MIF) and tumor necrosis factor-α. The meta-analysis indicated that CXCL12 rs1801157 (AG vs GG: OR = 1.99; 95%CI = 1.20–3.30; p = 0.008; AA + AG vs GG: OR = 1.92; 95%CI = 1.18–3.12; p = 0.009), TLR6 rs5743810 (TC vs TT: OR = 0.58; 95%CI = 0.39–0.85; p = 0.005), IL-10 rs1800871 (TC vs CC: OR = 1.19; 95%CI = 1.01–1.41; p = 0.044), rs1800872 (AC vs AA: OR = 1.53; 95%CI = 1.22–1.92; p < 0.001) and MIF rs755622 (CG versus GG: OR = 1.33; 95%CI = 1.07–1.67; p = 0.012) polymorphisms were associated with the risk of childhood leukemia. No significant correlations were found between SNPs in other genes and the childhood leukemia risk. Subgroup analyses of rs1800871 and rs1800872 confirmed the conclusions obtained in their overall meta-analytical processes.Conclusion: CXCL12 rs1801157, TLR6 rs5743810, IL-10 rs1800871, rs1800872 and MIF rs755622 polymorphisms may represent candidate biomarkers for the risk prediction of childhood leukemia.